MODIFICATION AND REENGINEERING OF ELECTRONIC FISH AGGREGATING DEVICE AS A FISHING TOOLS BASED ON LED ILLUMINANCE - Arif Baswantara; Indra Jaya; Roza Yusfiandayani (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Fish Aggregating Devices (FADs) is generally made from foliage like a leaf of coconut, palm and nut, but with the development of marine and fishing technology, the FADs could be made electronic ally. Electronic FADs had been developed by using light and sound as an attractor, and was able to aggregate fish but the catch harvest was still relatively low compared with lift net lamp. In this paper we describe the recent development of electronic FADs. The new electronic FADs has 120 watts total power of LEDs as attractor, 12V 12Ah battery as the energy resources, and HDPE as the body of FADs. The lighting of the new is either blue – red light color (RE1) or red-white light color (RE2). The two kinds of lighting are tested and compared and its light distribution underwater case measured in term of the value of luminous flux. The results showed that new FADs work well in the water with light penetration of RE1 was better than RE2. Keywords: FADs, instrument, fishing, light